Minutes of General Council (extract)
010-0094-001 EXTRACT FROM THE MINUTES OF GENERAL COUNCIL AT PLYMOUTH 3rd TO 11th SEPTEMBER ,1936 259. SPAIN. Telegram was read from Viscountess Hastings, dated 8th September, 1936,(which had already appeared in the Press) giving message from Viscount Churchill who was in Barcelona, stating that he had received constant proofs that Italians and Germans were steadily supplying the rebels with armaments and services. The telegram was NOTED. 292/946/10/103